(3EOQGI GdEfJGL hGdYedjGJs - (3CMeO(B, (3GdjSGQjs ((3YeGf(B:s (3OGQ GdHOGjI(B,s, 2006)
(3GdfXGe GdeZdb, GfJGL GdSdY hJbOje GdNOeGJ, GdefJL, GdQbGHI Ydi GdLhOI, CSGSjGJ GdQbGHI Ydi GdLhOI, GNJjGQ GdehbY hGdJUeje GdOGNdj ddeUfY, JNWjW GdGfJGLs
(3HHdjhZQGajG(B: (3U(B.210s
Keywords: (3GdGOGQIs; (3GdGfJGLs; (3GdQbGHIs; (3VHW GdLhOIs